Stifin Test Sebagai Alternatif Pemetaan Potensi Siswa Dalam Pembelajaran Berdiferensiasi Kurikulum Merdeka: The Stifin Test as an Alternative to Mapping Student Potential in Independent Curriculum Differentiated Learning - Ahmad Fahimi; Mochammad Ronaldy Aji Saputra; Suryadi (Sociocouns: Journal of Islamic Guidance and Counseling, 2023)
In 2022 the government of the Republic of Indonesia launched a Kurikulum Merdeka to respond to educational challenges in the post-Covid-19 pandemic era. The Kurikulum Merdeka puts forward a learning approach that gives freedom to students to choose the focus of the lesson they are interested in. This approach gave birth to differentiated learning. This study aimed to explain Farid Poniman's STIFIn Test concept as an alternative to mapping carried out by the teacher to apply differentiated learning. This study uses the library study method, in which the researcher describes in detail the concept of the STIFIn Test from various references. Then the researchers looked for suitability and relevance regarding the research results on differentiation learning and the STIFIn Test through grounded theory. The results showed five types of STIFIn Test intelligence machines: Sensing, Thinking, Intuiting, Feeling, and Instinct. These five types give rise to diversity in learning readiness, interests, and learning styles so that they can be used as an alternative to differentiated learning mapping. This test uses the fingerprint scan method. The results of the fingerprint scan produce the type of machine intelligence and student genetic personality which will then be mapped in a categorization manner so that teachers can easily carry out differentiated learning activities in terms of content, process, product, and learning environment. Thus the STIFIn Test is very relevant as an alternative mapping in implementing differentiation learning in the Kurikulum Merdeka era.